A combined method of neutron activation analysis and radiometric measurements for U-234 and U-238 determination in soil samples of low uranium concentration - Montoya, Eduardo (2011)
A method that combines the use of non-destructive neutron activation analysis and high-resolution spectrometry has been developed for determination of the activities of U-234 and U-238 in geological samples of low uranium content. The U-238 content is determined by k0-based neutron activation analysis, whereas the U-234/U-238 relationship is measured by spectrometry after isolation and electrodeposition of the uranium extracted from a lixiviation with 6 M HCl. The main advantage of the method is the simplicity of the chemical operations, including the fact that the steps destined to assure similar chemical state for the tracer and the uranium species present in the sample are not necessary. The method was applied to soil samples from sites of the north Peru coast. Uranium concentration range 3 to 40 mg/kg and the isotopic composition correspond to natural uranium, with about 10 % uncertainty.